A chiral 4-polytope in Rsup3 - Pellicer, Daniel (Ars mathematica contemporanea, 2017)
In this paper we describe an infinite chiral 4-polytope in the Euclidean 3-space. This builds on previous work of Bracho, Hubard and the author, where a finite chiral 4- polytope in the Euclidean 4-space is constructed. These two polytopes show that there are finite and infinite chiral polytopes of full rank as defined by McMullen.
Keywords: kiralen 4-politop; politop polnega ranga